Impact assessment of Consortium for e-Resources in Agriculture (CeRA) on research productivity of agricultural universities in India - VEERANJANEYULU, K; AGRAWAL, R C; RATHINASABAPATHY, G; SINGH, NIRMAL (The Indian Journal of Agricultural Sciences, 2025)
This study aims to assess the extent of usage of Consortium for e-Resources in Agriculture (CeRA) and its impact on overall research productivity of Indian Agricultural Universities (AUs). The data was retrieved from CeRA and SCOPUS. The study is limited to 61 AUs during the period 2015–2021, and excludes ICAR research institutions. The results revealed that the top 10 universities accounted for 50.02% of the total downloads from CeRA. The top nine universities in terms of publication output contributed 50.71% of total number of publications produced by all AUs combined. Furthermore, 73% of the top 10 highly cited papers of each of the top 20 AUs, were published after the implementation of CeRA. Universities and institutions that have high CeRA download activity, but relatively low research output, need to be sensitized about this gap, encouraging them to optimally utilise CeRA resources more effectively to enhance research productivity.